Preparation process of heat-resistant anti-cracking concrete
By using calcium carbonate whiskers and water-reducing agents to prepare suspensions in concrete, and combining anatase and fly ash to treat PVA fibers, the problem of insufficient bonding ability between fibers and concrete is solved, and the pressure resistance and crack resistance of concrete are significantly improved. Performance and toughness.
Patent Information
- Application Number
- CN202411482460.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-23
AI Technical Summary
When the prior art adds fibers to concrete, the fibers are not effectively processed, resulting in insufficient bonding ability between the fibers and concrete, limiting the improvement of crack and compressive resistance.
Calcium carbonate whiskers and water-reducing agents are used to prepare suspensions, and PVA fibers are treated with anatase ore and fly ash, combined with VAE emulsion to modify the fibers to improve the bonding strength between the fibers and concrete.
Through the improved process, the uniform mixing and combination of PVA fiber and powder is improved, which significantly improves the compression and anti-cracking performance and toughness of concrete.
Smart Images

Figure CN119349939A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a preparation process of heat-resistant and crack-resistant concrete. Background Art
[0002] Anti-crack concrete is a specially formulated concrete designed to reduce or prevent cracks that occur during the hardening process. Concrete cracking is usually caused by factors such as shrinkage, temperature changes, drying, uneven settlement or internal stress. To improve the crack resistance of concrete, fibers are often added to the concrete to increase its tensile strength, thereby preventing cracks from forming.
[0003] However, the existing technology generally directly adds steel fibers or polypropylene fibers to concrete without processing the fibers, which results in poor bonding between the fibers and concrete and limited improvement in crack resistance and compression resistance. Summary of the invention
[0004] In view of the deficiencies in the prior art, the object of the present invention is to provide a preparation process of heat-resistant and crack-resistant concrete.
[0005] A preparation process of heat-resistant and crack-resistant concrete comprises the following steps:
[0006] S1: Preparation of suspension
[0007] Dissolving a water reducing agent in deionized water to obtain a dispersion solvent, adding calcium carbonate whiskers into the dispersion solvent, and performing ultrasonic dispersion to obtain a suspension;
[0008] S2: Preparation and treatment of PVA fibers
[0009] Anatase ore and fly ash are mixed, mechanically stirred and then ball-milled to obtain a mixed powder, the mixed powder is added to a suspension and stirred to obtain a modified solution, the modified solution, PVA and distilled water are mixed and stirred evenly to obtain a spinning solution, the spinning solution is added to a spinning machine, and a solution spinning technology is used to prepare PVA fibers through vacuum degassing, coagulation molding, thermal stretching and thermal drawing molding;
[0010] S3: PVA fiber modified by VAE emulsion
[0011] A mixed solution is prepared by taking butadiene styrene emulsion, boric anhydride and water, and the VAE emulsion is diluted to a VAE solution, and all of the VAE solution is added to the mixed solution to obtain a dispersed solution, and the treated PVA fiber is completely immersed in the dispersed solution, ultrasonically treated, and then placed in an oven for drying to obtain a dry fiber for standby use;
[0012] S4: Preparation of concrete
[0013] 5-30% by mass of aggregate, 20-60% by mass of concrete, 1-15% by mass of dry fiber and 1-5% by mass of admixture are mixed and stirred evenly to obtain heat-resistant and crack-resistant concrete.
[0014] Furthermore, step S1 of preparing the suspension comprises the following steps:
[0015] S1.1: dissolving the water reducing agent in deionized water at a volume ratio of 1:(5-10) to obtain a dispersion solvent;
[0016] S1.2: Add calcium carbonate whiskers into a dispersing solvent, disperse by ultrasonic for 15-20 minutes, and mechanically stir at 2200-2250 rpm for 15-20 minutes to obtain a suspension.
[0017] Further, step S2 prepares and treats PVA fibers, comprising the following steps:
[0018] S2.1: Anatase ore and fly ash are mixed, mechanically stirred for 2-5 minutes, and then ball milled for 25-30 minutes to obtain a mixed powder;
[0019] S2.2: Add the mixed powder into the suspension at a solid-liquid ratio of 1:(2-3), and mechanically stir for 5-15 minutes to obtain a modified solution;
[0020] S2.3: mixing the modified solution, PVA and distilled water in a volume ratio of 1:1:(1-3) and stirring evenly to obtain a spinning solution;
[0021] S2.4: Add the spinning solution into the spinning machine, adopt the solution spinning technology with a spinneret of 0.08mm diameter, vacuum degassing for 24h, coagulation molding with saturated Na2SO4 aqueous solution, thermal stretching and heat drawing to prepare the processed PVA fiber.
[0022] Further, step S3 VAE emulsion modification treatment of PVA fiber comprises the following steps:
[0023] S3.1: 50 parts by mass of styrene butadiene emulsion, 5 parts by mass of boric anhydride and water are prepared into 350 parts by volume of a mixed solution;
[0024] S3.2: Dilute 50 parts by mass of VAE emulsion to 400 parts by volume of VAE solution, and add all of it to the mixed solution, stir evenly, and then use ultrasonic treatment for 0.5-1h to obtain a dispersed solution;
[0025] S3.3: The treated PVA fibers are completely immersed in the dispersion solution and treated with ultrasound for 15-20 min;
[0026] S3.4: Then place it in a low-temperature oven at 25-28°C for 6-8 hours, take it out of the oven, stir it with a glass rod for 2-5 minutes, and then place it in a low-temperature oven for 40-48 hours until it is completely dried to obtain dry fiber for use.
[0027] Furthermore, the water reducing agent in step S1.1 is a polycarboxylic acid-based high-efficiency water reducing agent.
[0028] Furthermore, in step S1.2, the solid-liquid ratio of the calcium carbonate whiskers to the dispersion solvent is 1:(2-3).
[0029] Furthermore, in step S2.1, the mass ratio of anatase ore to fly ash is 1:(2-5).
[0030] Furthermore, the frequency of the ultrasonic treatment in step S3.2 and step S3.3 is 40 kHz.
[0031] Furthermore, the aggregate in step S4 is prepared by mixing recycled construction aggregate, slag and crushed stone in a mass ratio of 1:2:3.
[0032] Furthermore, the additive in step S4 is one or more of water reducing agent, phenol, polyvinyl alcohol, acetate, glycerol and polyacrylate.
[0033] Compared with the prior art, the present invention has at least the following beneficial effects:
[0034] 1. The present invention uses calcium carbonate whiskers and a water reducing agent to prepare a suspension, and uses anatase and fly ash to treat PVA fibers. The water reducing agent can reduce the water demand of the material and improve the fluidity of the slurry, so that the PVA fibers and powders are evenly mixed. The anatase powder and fly ash can be evenly distributed in the slurry and then coated on the PVA fibers. The tiny fly ash particles will attract each other, so that the treated PVA fibers can be closely combined with each other, thereby improving the compressive and anti-cracking properties of the concrete material.
[0035] 2. The present invention modifies the treated PVA fiber by VAE emulsion. After the VAE emulsion is introduced, the emulsion will diffuse into the treated PVA fiber, smoothing the rough surface of PVA and improving the bonding performance between the dephosphorized PVA fiber and the aggregate, thereby improving the toughness of the concrete and the effect of heat resistance and crack prevention. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] The accompanying drawings, which are incorporated herein and constitute a part of the specification, illustrate embodiments of the present disclosure and, together with the description, further serve to explain the principles of the present disclosure and to enable those skilled in the relevant art to make and use the present disclosure.
[0037] Figure 1The present invention is a flow chart of a process for preparing heat-resistant and crack-resistant concrete used in an embodiment of the present invention. DETAILED DESCRIPTION
[0038] Embodiment 1:
[0039] A preparation process of heat-resistant and crack-resistant concrete, such as Figure 1 As shown, the following steps are included:
[0040] S1: Preparation of suspension
[0041] S1.1: dissolving a polycarboxylic acid high-efficiency water reducer in deionized water at a volume ratio of 1:5 to obtain a dispersion solvent;
[0042] S1.2: Add calcium carbonate whiskers to a dispersing solvent, with a solid-liquid ratio of calcium carbonate whiskers to dispersing solvent of 1:2, and disperse by ultrasonic for 15 minutes, while mechanically stirring at 2250 rpm for 15 minutes to obtain a suspension;
[0043] S2: Preparation and treatment of PVA fibers
[0044] S2.1: Anatase ore and fly ash are mixed in a mass ratio of 1:2, mechanically stirred for 2 minutes, and then ball milled for 30 minutes to obtain a mixed powder;
[0045] S2.2: Add the mixed powder into the suspension at a solid-liquid ratio of 1:3, and mechanically stir for 15 min to obtain a modified solution;
[0046] S2.3: mixing the modified solution, PVA and distilled water in a volume ratio of 1:1:2 and stirring evenly to obtain a spinning solution;
[0047] S2.4: PVA fibers were prepared by solution spinning technology using a spinneret with a diameter of 0.08 mm, vacuum degassing for 24 hours, coagulation molding with saturated Na2SO4 aqueous solution, thermal stretching and hot drawing.
[0048] S3: PVA fiber modified by VAE emulsion
[0049] S3.1: 50 parts by mass of styrene butadiene emulsion, 5 parts by mass of boric anhydride and water are prepared into 350 parts by volume of a mixed solution;
[0050] S3.2: 50 parts by mass of VAE emulsion is diluted to 400 parts by volume of VAE solution, and all of it is added to the mixed solution, and after stirring evenly, ultrasonic treatment is performed at 40 kHz for 1 hour to obtain a dispersed solution;
[0051] S3.3: The treated PVA fibers were completely immersed in the dispersion solution and treated with 40kHz ultrasound for 20min;
[0052] S3.4: Then place it in a low-temperature oven at 25°C for 6 hours, take it out of the oven, stir it with a glass rod for 5 minutes, and then place it in a low-temperature oven for 48 hours until it is completely dried to obtain dry fiber for use.
[0053] S4: Preparation of concrete
[0054] 20% by mass of aggregate, 60% of concrete, 15% of dry fiber and 5% of admixture are mixed and stirred evenly. The aggregate is a mixture of recycled building aggregate, slag and crushed stone in a mass ratio of 1:2:3. The admixture is polyvinyl alcohol, glycerol and polyacrylate to obtain heat-resistant and crack-resistant concrete.
[0055] Embodiment 2:
[0056] A preparation process of heat-resistant and crack-resistant concrete, such as Figure 1 As shown, the following steps are included:
[0057] S1: Preparation of suspension
[0058] S1.1: Dissolve the polycarboxylic acid high-efficiency water reducer in deionized water at a volume ratio of 1:5 to obtain a dispersion solvent.
[0059] S1.2: adding calcium carbonate whiskers to a dispersing solvent, wherein the solid-liquid ratio of calcium carbonate whiskers to the dispersing solvent is 1:2, and ultrasonically dispersing for 20 minutes, while mechanically stirring at 2200 rpm for 20 minutes, to obtain a suspension;
[0060] S2: Preparation and treatment of PVA fibers
[0061] S2.1: Mix anatase ore and fly ash in a mass ratio of 1:2, mechanically stir for 5 minutes, and then ball mill for 25 minutes to obtain a mixed powder.
[0062] S2.2: Add the mixed powder into the suspension at a solid-liquid ratio of 1:3, and mechanically stir for 10 minutes to obtain a modified solution.
[0063] S2.3: mixing the modified solution, PVA and distilled water in a volume ratio of 1:1:2 and stirring evenly to obtain a spinning solution;
[0064] S2.4: PVA fibers were prepared by solution spinning technology using a spinneret with a diameter of 0.08 mm, vacuum degassing for 24 hours, coagulation molding with saturated Na2SO4 aqueous solution, thermal stretching and hot drawing.
[0065] S3: PVA fiber modified by VAE emulsion
[0066] S3.1: Take 50 parts by mass of styrene-butadiene emulsion, 5 parts by mass of boric anhydride and water to prepare a mixed solution of 350 parts by volume,
[0067] S3.2: Dilute 50 parts by mass of VAE emulsion to 400 parts by volume of VAE solution, and add all of it to the mixed solution. After stirring evenly, use 40kHz ultrasonic treatment for 1 hour to obtain a dispersed solution.
[0068] S3.3: The treated PVA fibers were completely immersed in the dispersion solution and treated with 40kHz ultrasound for 20min.
[0069] S3.4: Then place it in a low-temperature oven at 28°C for 8 hours, take it out of the oven, stir it with a glass rod for 5 minutes, and then place it in a low-temperature oven for 40 hours until it is completely dried to obtain dry fiber for use.
[0070] S4: Preparation of concrete
[0071] 20% by mass of aggregate, 60% of concrete, 15% of dry fiber and 5% of admixture are mixed and stirred evenly. The aggregate is a mixture of recycled building aggregate, slag and crushed stone in a mass ratio of 1:2:3. The admixture is polyvinyl alcohol, glycerol and polyacrylate to obtain heat-resistant and crack-resistant concrete.
[0072] Embodiment 3:
[0073] A preparation process of heat-resistant and crack-resistant concrete, such as Figure 1 As shown, the following steps are included:
[0074] S1: Preparation of suspension
[0075] S1.1: Dissolve the polycarboxylic acid high-efficiency water reducer in deionized water at a volume ratio of 1:10 to obtain a dispersion solvent.
[0076] S1.2: Add calcium carbonate whiskers to a dispersing solvent, wherein the solid-liquid ratio of calcium carbonate whiskers to dispersing solvent is 1:3, and disperse by ultrasonic for 15 minutes, while mechanically stirring at 2250 rpm for 15 minutes to obtain a suspension;
[0077] S2: Preparation and treatment of PVA fibers
[0078] S2.1: Mix anatase ore and fly ash in a mass ratio of 1:3, mechanically stir for 2 minutes, and then ball mill for 30 minutes to obtain a mixed powder.
[0079] S2.2: Add the mixed powder into the suspension at a solid-liquid ratio of 1:1, and mechanically stir for 15 minutes to obtain a modified solution.
[0080] S2.3: The modified solution, PVA and distilled water are mixed in a volume ratio of 1:1:3 and stirred evenly to obtain a spinning solution;
[0081] S2.4: PVA fibers were prepared by solution spinning technology using a spinneret with a diameter of 0.08 mm, vacuum degassing for 24 hours, coagulation molding with saturated Na2SO4 aqueous solution, thermal stretching and hot drawing.
[0082] S3: PVA fiber modified by VAE emulsion
[0083] S3.1: Take 50 parts by mass of styrene-butadiene emulsion, 5 parts by mass of boric anhydride and water to prepare a mixed solution of 350 parts by volume,
[0084] S3.2: Dilute 50 parts by mass of VAE emulsion to 400 parts by volume of VAE solution, and add all of it to the mixed solution. After stirring evenly, use 40kHz ultrasonic treatment for 1 hour to obtain a dispersed solution.
[0085] S3.3: The treated PVA fibers were completely immersed in the dispersion solution and treated with 40kHz ultrasound for 20min.
[0086] S3.4: Then place it in a low-temperature oven at 25°C for 6 hours, take it out of the oven, stir it with a glass rod for 5 minutes, and then place it in a low-temperature oven for 48 hours until it is completely dried to obtain dry fiber for use.
[0087] S4: Preparation of concrete
[0088] 20% by mass of aggregate, 60% of concrete, 15% of dry fiber and 5% of admixture are mixed and stirred evenly. The aggregate is a mixture of recycled building aggregate, slag and crushed stone in a mass ratio of 1:2:3. The admixture is polyvinyl alcohol, glycerol and polyacrylate to obtain heat-resistant and crack-resistant concrete.
[0089] Comparative Example 1:
[0090] Compared with Example 1, Comparative Example 1 is commercially available concrete.
[0091] Comparative Example 2:
[0092] Compared with Example 1, the difference of Comparative Example 2 is that no water reducing agent is added in step S1, but a polycarboxylic acid dispersant is used, specifically: "S1.1: dissolving the polycarboxylic acid dispersant in deionized water at a volume ratio of 1:5 to obtain a dispersion solvent,
[0093] S1.2: Add calcium carbonate whiskers to a dispersing solvent with a solid-liquid ratio of calcium carbonate whiskers to the dispersing solvent of 1:2, perform ultrasonic dispersion for 15 minutes, and mechanically stir at 2250 rpm for 15 minutes to obtain a suspension. The prepared heat-resistant and crack-resistant concrete is recorded as Comparative Example 2.
[0094] Comparative Example 3
[0095] Compared with Example 1, the difference of Comparative Example 3 is that in step S2, no anatase ore is added, but all fly ash is added, specifically: “S2.1: mechanically stirring the fly ash for 2 minutes, and then ball milling for 30 minutes to obtain a mixed powder;
[0096] S2.2: Add the mixed powder into the suspension at a solid-liquid ratio of 1:3, and mechanically stir for 15 min to obtain a modified solution;
[0097] S2.3: mixing the modified solution, PVA and distilled water in a volume ratio of 1:1:2 and stirring evenly to obtain a spinning solution;
[0098] S2.4: PVA fibers were prepared by solution spinning technology with a spinneret having a diameter of 0.08 mm, vacuum degassing for 24 h, solidification molding with saturated Na2SO4 aqueous solution, hot stretching and hot drawing. The prepared heat-resistant and crack-resistant concrete was recorded as Comparative Example 3.
[0099] Comparative Example 4
[0100] Compared with Example 1, the difference of Comparative Example 4 is that in step S2, fly ash is not added, but anatase ore is added entirely, specifically: “S2.1: mechanically stirring the anatase ore for 2 minutes, and then ball milling for 30 minutes to obtain a mixed powder;
[0101] S2.2: Add the mixed powder into the suspension at a solid-liquid ratio of 1:3, and mechanically stir for 15 min to obtain a modified solution;
[0102] S2.3: mixing the modified solution, PVA and distilled water in a volume ratio of 1:1:2 and stirring evenly to obtain a spinning solution;
[0103] S2.4: PVA fibers were prepared by solution spinning technology with a spinneret having a diameter of 0.08 mm, vacuum degassing for 24 h, solidification molding with saturated Na2SO4 aqueous solution, hot stretching and hot drawing. The prepared heat-resistant and crack-resistant concrete was recorded as Comparative Example 4.
[0104] The compressive strength of the embodiments and comparative examples was tested using the method in GB / T50081-2019 "Standard for Experimental Methods of Mechanical Properties of Concrete", as shown in Table 1.
[0105] Table 1
[0106] Compressive strength(MPa) Example 1 49.6 Example 2 49.3 Example 3 48.7 Comparative Example 1 46.7 Comparative Example 2 41.3 Comparative Example 3 40.4 Comparative Example 4 39.1
[0107] It can be seen that Example 1 has the highest compressive strength, which is 49.6 MPa. The higher the compressive strength, the greater the pressure that the concrete can withstand and the less likely it is to break.
[0108] The compressive strengths of Example 2 and Example 3 are 49.3 MPa and 48.7 MPa respectively, while the compressive strength of the commercially available product comparative example 1 is 46.7 MPa, indicating that the heat-resistant and crack-resistant concrete prepared by the present invention has better compressive performance.
[0109] The compressive strength of comparative example 2 is 41.3 MPa, which indicates that the water reducer can reduce the water demand of the material and improve the fluidity of the slurry, so that the PVA fiber and powder can be mixed evenly, and the anatase ore powder and fly ash can be evenly distributed in the slurry, thereby improving the compressive and anti-cracking properties of the concrete material.
[0110] The compressive strengths of Comparative Examples 3 and 4 are 40.4 MPa and 39.1 MPa, respectively, indicating that the treatment effect of anatase ore alone or fly ash alone on PVA fibers is not as good as the treatment effect of anatase ore and fly ash mixed on PVA fibers. Anatase ore powder and fly ash need to be coated on the surface of PVA fibers, and single powders are prone to agglomeration and thus cannot evenly coat the PVA fibers. The mixed powders have different particle sizes and are not easy to aggregate, so they are evenly coated on the surface of the PVA fibers for treatment, allowing the treated PVA fibers to be tightly bonded to each other, thereby improving the compressive and anti-cracking properties of concrete materials.
[0111] Table 2
[0112]
[0113] It can be seen that the flexural strengths of Example 1, Example 2 and Example 3 are 8.1 MPa, 7.8 MPa and 7.7 MPa respectively, while the comparative example 1 of the commercially available product is not bad, but not as high as the examples, only 7.5 MPa. It can be seen that the flexural strength of the examples is higher than that of the commercially available products.
[0114] The service life of comparative example 2 is only 6.4 MPa, because no water reducing agent is added, the slurry fluidity is low, so that the PVA fiber and powder cannot be mixed evenly, and the compressive and anti-cracking properties of the concrete material cannot be improved.
[0115] The service life of comparative examples 3 and 4 is 6.1 MPa and 5.8 MPa respectively, indicating that the strength of anatase ore or fly ash alone is not as good as the combination of the two. It can be seen that both anatase ore and fly ash have a certain ability to improve the anti-cracking effect of concrete.
[0116] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A process for preparing heat-resistant and crack-resistant concrete, characterized in that: The steps include: S1: Preparation of suspension Dissolving a water reducing agent in deionized water to obtain a dispersion solvent, adding calcium carbonate whiskers into the dispersion solvent, and performing ultrasonic dispersion to obtain a suspension; S2: Preparation and treatment of PVA fibers Anatase ore and fly ash are mixed, mechanically stirred and then ball-milled to obtain a mixed powder, the mixed powder is added to a suspension and stirred to obtain a modified solution, the modified solution, PVA and distilled water are mixed and stirred evenly to obtain a spinning solution, the spinning solution is added to a spinning machine, and a solution spinning technology is used to prepare PVA fibers through vacuum degassing, coagulation molding, thermal stretching and thermal drawing molding; S3: PVA fiber modified by VAE emulsion A mixed solution is prepared by taking butadiene styrene emulsion, boric anhydride and water, and the VAE emulsion is diluted to a VAE solution, and all of the VAE solution is added to the mixed solution to obtain a dispersed solution, and the treated PVA fiber is completely immersed in the dispersed solution, ultrasonically treated, and then placed in an oven for drying to obtain a dry fiber for standby use; S4: Preparation of concrete 5-30% by mass of aggregate, 20-60% by mass of concrete, 1-15% by mass of dry fiber and 1-5% by mass of admixture are mixed and stirred evenly to obtain heat-resistant and crack-resistant concrete.
2. The process for preparing heat-resistant and crack-resistant concrete according to claim 1, characterized in that: step S1 prepares a suspension, comprising the following steps: S1.1: dissolving the water reducing agent in deionized water at a volume ratio of 1:(5-10) to obtain a dispersion solvent; S1.2: Add calcium carbonate whiskers into a dispersing solvent, disperse by ultrasonic for 15-20 minutes, and mechanically stir at 2200-2250 rpm for 15-20 minutes to obtain a suspension.
3. The preparation process of heat-resistant and crack-resistant concrete according to claim 2, characterized in that: Step S2 prepares and processes PVA fibers, comprising the following steps: S2.1: Anatase ore and fly ash are mixed, mechanically stirred for 2-5 minutes, and then ball milled for 25-30 minutes to obtain a mixed powder; S2.2: Add the mixed powder into the suspension at a solid-liquid ratio of 1:(2-3), and mechanically stir for 5-15 minutes to obtain a modified solution; S2.3: mixing the modified solution, PVA and distilled water in a volume ratio of 1:1:(1-3) and stirring evenly to obtain a spinning solution; S2.4: Add the spinning solution into the spinning machine, adopt the solution spinning technology with a spinneret of 0.08mm diameter, vacuum degassing for 24h, coagulation molding with saturated Na2SO4 aqueous solution, thermal stretching and heat drawing to prepare the processed PVA fiber.
4. The process for preparing heat-resistant and crack-resistant concrete according to claim 3, characterized in that: Step S3: treating the PVA fiber with VAE emulsion modification, comprising the following steps: S3.1: 50 parts by mass of styrene butadiene emulsion, 5 parts by mass of boric anhydride and water are prepared into 350 parts by volume of a mixed solution; S3.2: Dilute 50 parts by mass of VAE emulsion to 400 parts by volume of VAE solution, and add all of it to the mixed solution, stir evenly, and then use ultrasonic treatment for 0.5-1h to obtain a dispersed solution; S3.3: The treated PVA fibers are completely immersed in the dispersion solution and treated with ultrasound for 15-20 min; S3.4: Then place it in a low-temperature oven at 25-28°C for 6-8 hours, take it out of the oven, stir it with a glass rod for 2-5 minutes, and then place it in a low-temperature oven for 40-48 hours until it is completely dried to obtain dry fiber for use.
5. The process for preparing heat-resistant and crack-resistant concrete according to claim 4, characterized in that: The water reducing agent in step S1.1 is a polycarboxylic acid-based high-efficiency water reducing agent.
6. The process for preparing heat-resistant and crack-resistant concrete according to claim 5, characterized in that: In step S1.2, the solid-to-liquid ratio of calcium carbonate whiskers to the dispersion solvent is 1:(2-3).
7. A process for preparing heat-resistant and crack-resistant concrete according to claim 6, characterized in that: In step S2.1, the mass ratio of anatase ore to fly ash is 1:(2-5).
8. The process for preparing heat-resistant and crack-resistant concrete according to claim 7, characterized in that: The frequency of the ultrasonic treatment in step S3.2 and step S3.3 was 40 kHz.
9. The process for preparing heat-resistant and crack-resistant concrete according to claim 8, characterized in that: The aggregate in step S4 is prepared by mixing recycled construction aggregate, slag and crushed stone in a mass ratio of 1:2:
3.
10. A process for preparing heat-resistant and crack-resistant concrete according to claim 9, characterized in that: The additive in step S4 is one or more of water reducing agent, phenol, polyvinyl alcohol, acetate, glycerol and polyacrylate.
Citation Information
Patent Citations
PVA fiber reinforced cement-based composite material
CN105906261A
High-strength recycled concrete and preparation method thereof
CN111960766A
Anti-crack concrete and preparation method thereof
CN112028557A
Plateau region airport pavement concrete and preparation method thereof
CN115806420A
Anti-crack waterproof concrete and preparation method thereof
CN116553886A
Cited By
Anti-cracking concrete and production process thereof
CN122010503A
Anti-cracking concrete and its production process
CN122010503B